Daily uptake of mycotoxins – TDI might not be protective for nursed infants. (5th August 2017) - Degen, G.H.; Partosch, F.; Muñoz, K.; Gundert-Remy, U.
Highlights: Mycotoxins can be excreted with breast milk resulting in exposure of nursed infants. Lactational transfer was estimated using toxicokinetic data and in their absence in silico methods. Estimated infant exposure to mycotoxins can exceed the age-adjusted TDI values. Exceedance is particularly pronounced for ochratoxin A. Abstract: Exclusive breast feeding is recommended by international bodies for the first six months of life. Because of the presence of contaminants, breast feeding might lead to toxicologically relevant exposure of the nursed child. Exposure towards mycotoxins is of specific interest because of their widespread occurrence in food and of their toxicological profile. We calculated the relationship between maternal intake at the level of the existing TDIs and the exposure in the nursed infants of several mycotoxins to evaluate whether maternal exposure at the TDI is also safe for the nursed infant. If published information was not available we used in silico methods for estimating toxicokinetic parameters and the lactational transfer. A single dose and a continuous daily intake scenario were considered. Maternal intake at the TDI exceeds the age-adjusted TDI (TDI/3) values for infants in case of deoxynivalenol and patulin in the single dose scenario. Exceedance is particularly pronounced for ochratoxin A in the continuous daily intake scenario (29.2 fold above the child adjusted TDI). According to published data in infants impaired kidney function may result from this exceedance. When setting a TDI, the safety of the exclusively nursed infant should be considered in the continuous daily intake scenario.